1989
DOI: 10.4319/lo.1989.34.7.1315
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of phosphorus, fish, and site effects on phytoplankton biomass and zooplankton

Abstract: We conducted an outdoor tank experiment of factorial design with three levels of phosphorus addition cross‐classified with two levels of mosquitofish (Gambusia affinis) at two lake sites, allowing us to examine both main effects and interaction effects of phosphorus, fish, and site on phytoplankton biomass and zooplankton. Phosphorus addition significantly increased total phosphorus concentration and chlorophyll and decreased Secchi depth. Fish significantly decreased cladoceran densities and Secchi depth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
1
10
0
1
Order By: Relevance
“…Mosquitofish and common carp were selected as members of the fish assemblage because they represent two fish consumer types found in lake communities. Mosquitofish is a carnivore that consumes zooplankton and benthic invertebrates (Hurlbert et al 1972;Hurlbert and Mulla 1981;Drenner et al 1989;Lancaster and Drenner 1990) and carp is a benthivore (Richardson et al 1990). Both species are distributed throughout the United States (Page and Burr 1991) and commonly co-occur with bluegill (Miranda 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitofish and common carp were selected as members of the fish assemblage because they represent two fish consumer types found in lake communities. Mosquitofish is a carnivore that consumes zooplankton and benthic invertebrates (Hurlbert et al 1972;Hurlbert and Mulla 1981;Drenner et al 1989;Lancaster and Drenner 1990) and carp is a benthivore (Richardson et al 1990). Both species are distributed throughout the United States (Page and Burr 1991) and commonly co-occur with bluegill (Miranda 1983).…”
Section: Methodsmentioning
confidence: 99%
“…In a series of deep large lakes, Hyatt & Stockner (1985) observed larger standing stocks of zooplankton and increased growth of salmon fry with added nutrients and Kelso (1985) found increased fish production with increased primary productivity. In contrast, in a series of tank mesocosms Drenner et al (1989) found no increases in zooplankton with increased nutrients. Likewise Bare Lake in Alaska received fertilizer additions which stimulated phytoplankton but zooplankton abundance did not change (Nelson & Edmondson, 1955).…”
Section: Regulation Of Lake Ecosystemsmentioning
confidence: 66%
“…La plupart des expériences ont été faites avec des poissons chassant à vue comme les menés, les crapets, les perchaudes, et les larves de dorés (VANNI, 1987 ;MAZUMDER er al., 1988 ;DRENNER et al, 1989DRENNER et al, , 1990PROULX étal., 1996). Elles ont permis de mettre en évidence des effets très variables des interactions nutriments x poissons sur la structure du plancton (composition taxonomique, structure en taille) ou certaines caractéristi-ques physico-chimiques.…”
Section: Tableauunclassified